Features of estimation of left ventricular geometry in patients with arterial hypertension - V. V. Syvolap; Ye. V. Novikov; V. A. Lysenko; A. O. Bogun (Patologìâ)
Aim: To compare the influence of the methods of calculating MMLV for Penn Convention and ASE on the distribution of left ventricular geometry types in patients with hypertension, to find out additional echographic criteria that will help to offset differences in the estimation of types of geometry.